Railways and manufacturing productivity in Italy after unification. (4th February 2020) - Pontarollo, Nicola; Ricciuti, Roberto
Abstract: This paper contributes to the debate on the effects of transport infrastructure endowment on productivity by adding a historical perspective. This allows us to address the issue in a proving ground where the effects of the existing stock of infrastructure are negligible. At the time of unification, the Kingdom of Italy initiated a large infrastructure project to build railways. We find that railways had a positive effect on manufacturing productivity over the period 1871–1911. Railways also had strong spillover effects in neighboring provinces so that provinces that started with a higher endowment of railways benefited more than those who were newly endowed.